The story of clobenpropit and CXCR4: can be an effective drug in cancer and autoimmune diseases? - Abbasifard, Mitra; Bagherzadeh, Kowsar; Khorramdelazad, Hossein (Frontiers in Pharmacology, 2024)
Clobenpropit is a histamine H3 receptor antagonist and has developed as a potential therapeutic drug due to its ability to inhibit CXCR4, a chemokine receptor involved in autoimmune diseases and cancer pathogenesis. The CXCL12/CXCR4 axis involves several biological phenomena, including cell proliferation, migration, angiogenesis, inflammation, and metastasis.Accordingly, inhibiting CXCR4 can have promising clinical outcomes in patients with malignancy or autoimmune disorders. Based on available knowledge, Clobenpropit can effectively regulate the release of monocyte-derived inflammatory cytokine in autoimmune diseases such as juvenile idiopathic arthritis (JIA), presenting a potential targeted target with possible advantages over current therapeutic approaches. This review summarizes the intricate interplay between Clobenpropit and CXCR4 and the molecular mechanisms underlying their interactions, comprehensively analyzing their impact on immune regulation. Furthermore, we discuss preclinical and clinical investigations highlighting the probable efficacy of Clobenpropit for managing autoimmune diseases and cancer. Through this study, we aim to clarify the immunomodulatory role of Clobenpropit and its advantages and disadvantages as a novel therapeutic opportunity.